2017
DOI: 10.7717/peerj.4172
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization and expression profiling ofNACtranscription factor genes under abiotic stresses in radish (Raphanus sativusL.)

Abstract: NAC (NAM, no apical meristem; ATAF, Arabidopsis transcription activation factor and CUC, cup-shaped cotyledon) proteins are among the largest transcription factor (TF) families playing fundamental biological processes, including cell expansion and differentiation, and hormone signaling in response to biotic and abiotic stresses. In this study, 172 RsNACs comprising 17 membrane-bound members were identified from the whole radish genome. In total, 98 RsNAC genes were non-uniformly distributed across the nine rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…The number of NAC genes in cultivated peanut (164) was larger than that in other plant species (for example, 105 in Arabidopsis [40], 141 in rice [41], and 101 in soybean [46]), which was approximately 1.56-fold than that in Arabidopsis, and a similar result was found in Populus [10]. The NAC gene density in A.duranensis, A. ipaensis and A.hypogaea (0.07/Mb, 0.05/Mb, 0.06/Mb) was lower than that in Arabidopsis (0.87/Mb) and rice (0.37/Mb) [11]. This may be attributed to Arachis large genome sizes, which suggested that the genome size and number of NAC family members were not always correlated.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The number of NAC genes in cultivated peanut (164) was larger than that in other plant species (for example, 105 in Arabidopsis [40], 141 in rice [41], and 101 in soybean [46]), which was approximately 1.56-fold than that in Arabidopsis, and a similar result was found in Populus [10]. The NAC gene density in A.duranensis, A. ipaensis and A.hypogaea (0.07/Mb, 0.05/Mb, 0.06/Mb) was lower than that in Arabidopsis (0.87/Mb) and rice (0.37/Mb) [11]. This may be attributed to Arachis large genome sizes, which suggested that the genome size and number of NAC family members were not always correlated.…”
Section: Discussionsupporting
confidence: 69%
“…2), suggesting that diversification and expansion of this subgroup occurred after the monocot-dicot divergence. This phenomenon has also been found in radish, Populus and other species [10,11].…”
Section: Phylogenetic Analysis and Expression Profiling Of Arachis Nasupporting
confidence: 66%
See 1 more Smart Citation
“…In several crops, specific families of transcription factors are candidates to mediate heat stress response in roots. Thus, HD-ZIP and NAC transcription factors are induced by heat stress in potato and radish (Karanja et al, 2017;Li et al, 2019). In batata, ABF4, an ABA-responsive element binding factor that is up-regulated under heat stress promotes the expression of several stress responsive genes and mediate root elongation response .…”
Section: Genetic and Molecular Regulatory Pathwaysmentioning
confidence: 99%
“…Comparative genomic and gene functional analyses have indicated that NAC TFs underwent an expansion in the lineage of vascular plants [13]. Also, tracheid evolution is associated with a burst of structural diversity [14], which is probably related to NAC genes controlling SCW biosynthesis in vascular plants, comprising seedless vascular plants, gymnosperms, and angiosperms [15]. Noticeably, plant species that are structurally less complex contain significantly fewer NAC genes, such as the model bryophyte Physcomitrella patens (Hedw.)…”
Section: Introductionmentioning
confidence: 99%